Quasi-Experimental Study on Papua Cultural-Based Learning Strategies with Canva Media in Papua Elementary Schools - Suherman Suherman; Harsono Harsono; Choiriyah Widiyasari; Laili Etika Rahmawati; Minsih Minsih (Eduvest - Journal of Universal Studies, 2025)
Improving learning independence and academic achievement among elementary school students in Papua remains a challenge, especially considering that the rich cultural heritage of Papua has not been well integrated into education. This study aims to examine Papua Cultural-Based Learning Strategies (PCBLS) integrated with Canva media to enhance learning independence and academic achievement of elementary school students in Papua. The study employs a quasi-experimental design with a pre-test post-test approach. The research sample consists of 60 fourth-grade students at SD INPRES SIBENA 1, divided into 3 control classes and 3 experimental classes. The PCBLS intervention integrated with Canva media was implemented over one semester. The analysis results indicate that PCBLS integrated with Canva media effectively improves learning independence (t = 5.42, p < 0.01) and academic achievement (t = 6.21, p < 0.01) among elementary school students in Papua. The findings of this study demonstrate that PCBLS integrated with Canva media is an effective learning strategy to enhance learning independence and academic achievement of elementary school students in Papua. This encourages teachers to adopt this learning strategy and contributes new insights to educational science and teaching practices in Papua.